Using portfolios as a powerful strategy to foster and develop students writing skill in EFL - Daniel Albeiro Melgarejo M. (Corporación Universitaria Minuto de Dios, 2006)
This article emphasises on the use of portfolios as a powerful strategy to monitor the students' writing performance in EFL and foster their writing production by means of taking advantage of their interests and beliefs when creating different types of compositions. Some of the ideas included in this article come from a large project research carried out with children between 9 and 13 years old who were in the Intermediate level of "Cursos de Extensión" at Universidad Pedagó- gica Nacional. The data analysis component is still in process and it is part of the thesis proposed by the author for the Master in Applied Linguistics for the TEFL at Universidad Distrital "Francisco José de Caldas".